"It's Just Another Added Benefit": Women's Experiences with Employment-Based Egg Freezing Programs. Issue 1 (28th September 2020) - Miner, S. A.; Miller, W. K.; Grady, C.; Berkman, B. E.
Abstract: Background: In 2014, companies began covering the costs of egg freezing for their employees. The adoption of this benefit was highly contentious. Some argued that it offered women more reproductive autonomy, buying time to succeed in their careers and postpone childbearing. Others suggested this benefit might place inappropriate pressure on women, unduly influencing them to freeze their eggs to prioritize their career over reproduction. Although ethical problems with this benefit have been explored, there has not been research analyzing the perspectives of women working for companies that offer employer-based egg freezing. Furthermore, existing empirical studies often focus on the experiences of egg freezers rather than the young women thinking about, but not yet using, this technology. Methods: Through in-depth semi-structured interviews, we explore the perceptions and attitudes of 25 women employees of companies with employer-based egg freezing. Results: These women describe delaying childbearing for a multitude of reasons, including not having a partner, and the desire to achieve social and career goals. Many women did not know that their employers covered egg freezing before the interview (44%; 11/24), suggesting this benefit is not essential to their career and family-building decisions. While women did not describe pressure to use this technology, they did describe how this benefit would not solve the difficulties of becoming a mother while excelling in their careers. Conclusion: Although women may not feel pressure to freeze their eggs and delay childbearing, they still feel constricted in their reproductive options. While employer programs may offer women the ability to delay childbearing, many saw this delay as postponing problems with work-life balance rather than solving them. We suggest that sociocultural shifts, such as workplace daycare, flexible workplace hours, and acceptability of non-biological parenthood, might allow women to feel more empowered about their reproduction choices.